A Research on the Relationship of Social Intelligence and Cultural Intelligence with Leadership Styles - Serap Yalçınyigit; Hakkı Aktaş (Istanbul Business Research)
Technological and social changes have made the organizational nature more open and accessible than ever. In recent years, modern leadership styles are used to efficiently manage these radical changes, and social intelligence and cultural intelligence concepts are used to get an edge over these changes correctly. In this study, based on the interaction of different intelligence types with the leadership styles exhibited, the factors affecting the leadership style were examined. The concept of leadership was carefully considered by associating the sub-dimensions of social intelligence and cultural intelligence, and assessing them in terms of demographics. The research sample is selected as Technopark employees in Istanbul. The sample reflects one of the increasingly widespread Technology Development Zones in Turkey, and welcomes technological developments as well as foreign cultural companies within. By analyzing the obtained data from 354 participants with descriptive and explanatory statistical methods, the relationships between leadership styles in the Multi-Factor Leadership Questionnaire, a comprehensive leadership tendency measurement tool, and social intelligence and cultural intelligence have been revealed. In addition, the effects of social intelligence’s and cultural intelligence’s sub-dimensions on four different leadership styles, and demographic differentiations are detected. The research provides guiding outputs for future research and business reflections.